Analysis of Groundwater Quality on Public Health Around the Putri Cempo TPA, Mojosongo District, Surakarta - Putri Permatasari Dinda; Asty Pramudita Desma; Enos Berlin Gavriel; Rachmawati Siti; Firmansyah Fathoni; Sholiqin Muchammad (E3S Web of Conferences, 2023)
Over time, the population of living things continues to increase. This is of course in line with the increasing needs of living things. The population continues to grow, causing the need for water to increase. Putri Cempo TPA is a final disposal and shelter located in Mojosongo, Surakarta, Central Java. At this location there is a village directly adjacent to the landfill area, where there are concerns regarding contaminated water sources for sanitation, hygiene, and consumption facilities. The purpose of this study was to determine the quality of ground water used by residents for sanitation, hygiene, and consumption purposes, and to find a correlation between water quality and health data of local residents. This study uses a qualitative method with sampling. The data obtained from observations using the concept of area 1 with a distance (100-200 m), area II with a distance (200-400 m) and area III with a distance (400-600 m), interviews, as well as secondary data will be studied more deeply and will be explained in a holistic and 'circular' manner using a SWOT analysis approach. The results of this study indicate that most of the water parameters have met the standards set by the government. while the parameters of pH and suspended residue did not meet the standard. And there is a link between water quality conditions and public health, such as the incidence of Acute pharyngitis unspecified, fever of other and unknown origin, other forms of stomatitis, and other noninfective gastroenteritis and colitis which have symptoms such as fever, cough, decreased appetite, and diarrhea.